2016
DOI: 10.21620/ijfaas.2016123-29
|View full text |Cite
|
Sign up to set email alerts
|

Quality evaluation of yoghurt stabilized with sweet potato (Ipomoea batatas) and taro (Colocassia esculenta) starch

Abstract: Stabilizers are important component in manufactured products such as yoghurt. The addition of stabilizers improves body, texture, appearance, mouth feel and prevents technical defects such as synersis in yoghurts. In this study starch was extracted from plant sources (sweet potato, taro) with and without use of chemicals. Yoghurt was enriched with different levels of extracted starch. Yoghurt samples were analyzed for physicochemical and functional attributes such as pH, acidity, synersis, water holding capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
0
14
1
Order By: Relevance
“…This finding was similar to those reported by Malik et al [ 7 ], who confirmed that yogurt samples remained satisfactory during storage at 5 °C for 15 days for all sensory parameters due to the different concentration of starch extracted from Trapa bispinosa . In contrast, this present study was not in agreement with Sameen et al [ 12 ], who said that there was no statistical difference between adding a different concentration of starch in manufacturing yogurt and the control sample for all sensory parameters.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…This finding was similar to those reported by Malik et al [ 7 ], who confirmed that yogurt samples remained satisfactory during storage at 5 °C for 15 days for all sensory parameters due to the different concentration of starch extracted from Trapa bispinosa . In contrast, this present study was not in agreement with Sameen et al [ 12 ], who said that there was no statistical difference between adding a different concentration of starch in manufacturing yogurt and the control sample for all sensory parameters.…”
Section: Resultscontrasting
confidence: 99%
“…The overall acceptability of extracted potato starch in yogurt manufacturing was carried out by a panel of 20 trained panelists from the staff of the Food Science Department, College of Agriculture, University of Basrah according to the method described by Sameen et al [ 12 ]. Appearance, body and texture, flavor, and acidity were assessed for sensory evaluation of manufactured yogurt.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant origin stabilizers are considered to be the cheapest and they include the commonly used ones, such as corn starch. Starch is preferred in the yogurt industry, because it is a good thickener and its ability to reduce yogurt flaws by improving texture and make the product more appealing to consumers [12][13][14]. Starches, such as corn, sweet potato, potato, and chestnut, are commonly used by the yogurt industry at 0.25 to 1%".…”
Section: Introductionmentioning
confidence: 99%
“…The overall acceptability of tiger nut yoghurt manufactured was carried out by 20 panellists according to the method described by Sameen et al (2016). Appearance, colour, taste, smell, mouth-feel and general acceptability ranking were assessed for organoleptic evaluation; the mean of the manufactured yoghurt and of three popular market yoghurts was taken.…”
Section: Organoleptic Evaluationmentioning
confidence: 99%